Association between vitamin D and bone mineral density in post-menopausal women with metabolic syndrome - Dadonienė, Jolanta; Čypienė, Alma; Rinkūnienė, Egidija; Badarienė, Jolita; Burca, Jelizaveta; Sakaitė, Ieva; Kalinauskaitė, Goda; Kumpauskaitė, Vaiva; Laucevičius, Aleksandras (Acta medica Lituanica, 2015)
Background. The aim of this study was to identify the relation between vitamin D level and mineral bone density in post-menopausal women with metabolic syndrome. Materials and methods. This study included 100 post-menopausal women at age between 50 and 65 with metabolic syndrome. All participants underwent anthropometric measurements. Laboratory tests were performed to determine lipid profile, serum glucose, creatinine, C-reactive protein, vitamin D (25(OH) D), ionized calcium concentration and urine albumin / creatinine ratio. Bone mineral density of the lumbar spine (L1– L4) and total hip was measured by dual-energy X-ray absorptiometry. Results. According to the vitamin D concentration level in the blood all women were divided into four groups: the average failure was observed in 57%, mild failure in 33%, severe failure in 5%; and only 5% of women had normal vitamin levels. The mean 25(OH) D level was 47.40 ± 16.91 nmol/l. According to bone densitometry we found that 77% of all participants had normal bone mineral density, 22% had osteopenia and 5% were diagnosed with osteoporosis. No correlation was found between bone mineral density and 25(OH) D levels. We found a weak positive correlation between high density lipoprotein cholesterol and 25(OH) D (r = 0.3, p